PENGEMBANGAN PARIWISATA BUDAYA DESA YANG BERBASIS TRADISI DAN KEARIFAN LOKAL DI DESA NGEGEDHAWE: - Laura Priska Satina Batu; Veronika Ruba Pena; Bruno Rey Sonby Pantola; Veronika Ina Assan Boro (Journal Education and Government Wiyata, 2026)
The development of cultural tourism in Ngegedhawe Village prioritizes the use of local wisdom and tradition as the main attraction. The main issue in the development of cultural tourism in Ngegedhawe Village which prioritizes tradition and local wisdom is how to incorporate cultural values ​​and traditional practices of the community into attractive tourism products and experiences without sacrificing the authenticity and sustainability of the cultural heritage. This study aims to identify the potential for cultural and natural tourism, as well as the constraints in its management. The methods applied include socialization, interactive discussions, and training for the community. The findings show that active community involvement in tourism development can improve welfare and maintain the sustainability of cultural heritage. Through a collaborative approach, it is hoped that the tourism sector in Ngegedhawe can grow sustainably without harming local values.